Notice App: An android application to understand and identify students’ perspective - Kokalki, Mr. Abhilash.R.Ghagare, Mr. Lucky P. Bajaj , Mr. Siddharth A. (International Journal of Engineering and Computer Science, 2017)
— In older days college notices were displayed on wooden notice board that are mounted at different locations in college building [1]. Generally students were not aware about notices which are very time bounded and also not habitual to read notices regularly. As technological evolution done very rapidly, it is need to update with technology. Smart phones and android phones are now a days ease to use and everybody aware of its handling. In this paper, we proposed an android application to display different kind of notices organized into various categories such as department, TPO, office, sports, cultural, hostel etc. so that students will get all college notices anytime and anywhere. This application mainly focuses on update, delete notices and specific feedback generation using association rule on student dataset. We will try to find students perspective by analyzing specific feedback questionnaire.